Penurunan Kandungan Zat Besi Dalam Air Sumur Galian dengan Menggunakan Metode Aerasi - Putriani, Deka; Afliansyah, Eddwin Pratama; Karsina, Melan; Walid, Ahmad (TIN: Terapan Informatika Nusantara, 2020)
The concentration of manganese in natural water systems is generally less than 0.1 mg / l. If it exceeds 1 mg / l then it needs water treatment. Dug well water in Kumai Hilir Village, Central Kalimantan, has a Mn content of 2.02 mg / l, exceeding the quality standard based on the Minister of Health Decree No. 907 / Menkes / VII / SK / 2002. The research problem is how to reduce Mn levels in dug well water using a cascade with aeration process. The purpose of this study was to reduce the Mn level in dug well water by aeration process and to determine the effectiveness of the cascade aerator and bubble aerator in reducing Mn levels in dug well water. The research method is Quasy Experiment with Pre and Post Test Design. The research sample was taken using a grap sampling technique, the aeration process was carried out in one of the residents' houses and the Mn level examination in the laboratory. The results showed that the use of a cascade aerator gave better results in reducing the Mn content of dug well water by an average of 0.02 mg / l, which was in accordance with the quality standard with an effectiveness of 98.74%. Bubble aerators can reduce the Mn content of dug well water by an average of 0.43 mg / l, and 76.47% effectiveness. This result is not in accordance with the quality standard according to the Kepmenkes No 907 / Menkes / VII / SK / 2002, which is 0.1 mg / l. The conclusion of this research is the cascade aerator is more effective in reducing the Mn content of dug well water